Exilio y migración de retorno. Una reflexión comparativa para el caso colombiano. (2018)
This paper aims at exploring return migration’s phenomenon of Colombian exiles from a comparative lecture of what happened in the Southern Cone of Latin America during the military dictatorships. In this respect, a dialogue is established between different literary stories of exiles from the Southern Cone that show the existential complexity of the return process and, in some cases, the impossibility of returning. This dialogue will provide elements of analysis that will allow the understanding of exile as a rupture and return migration as a possibility that opens up in the post-conflict.